KERLIBATAN PEREMPUAN DALAM KEGIATAN SOSIAL KEMASYARAKATAN - Hastuti, Hastuti (Jurnal Penelitian Humaniora, 2015)
Abstract This research aims at studying the characteristics of social activities conducted by wives in two different accessibility villages. The populations of the research are 120 wives in bantarjo village and 83 wives in Kalitengah Lor village. The data are analyzed descriptively using percentage shown in tables. The result of the research shows that there are different characteristics of wives in those villages seen from education, job, and field management. The education level of wives in Bantarjo is better than that in Kalitengah lor. Field management does not always determine socio-economy condition of the people in Bantarjo. There are wives, in Bantarjo, who do not work. In Kalitengah Lor, all wives work. In Bantarjo, there are iincome generating activities beyond agriculture. In Kalitengah Lor, however, farming is the main financial income. Accessibility influences the social activities. Bantarjo’s accessibility is better than Kalitengah Lor’s. In bantarjo, cooperative mass working, kerja bakti, ritual-religious activities like bersih desa, kenduri to fix the road, water channel,irrigation channel, security post, mosque, burial aredone bymen or husband. On the contrary, in Kalitengah Lor, women or wives mostly do the activities above. The mean of time, in poor and upper household, used by wives in conducting social activities in bantarjo is less than in Kalitengah Lor. In the have families, the mean oftime used by wived in conducting social activities is bigger than that in Kalitengah Lor. Keywords: accessibility, social activity